2012
DOI: 10.1002/er.2956
|View full text |Cite
|
Sign up to set email alerts
|

A possible future fuel cell: the peroxide/peroxide fuel cell

Abstract: SUMMARY Hydrogen peroxide (H2O2) and the reduction/oxidation by‐products of peroxide are non‐toxic to humans and the environment. Simple, low‐concentration hydrogen‐peroxide solutions used as fuel and direct peroxide/peroxide fuel cells (DPPFCs) face significant challenges in the development of a new class of power generators. A power density of 10 mWcm−2 at a cell potential of 0.55 V have been achieved with a DPPFC composed of carbon‐paper‐supported nickel as the anode catalyst and carbon‐paper PbSO4 as the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Recent studies have shown that the use of hydrogen peroxide as an oxidant is quite helpful to solve the aforementionedproblems . First, due to the excellent kinetics of hydrogen peroxide in the reduction reaction, it is likely to use a non‐noble metal catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the use of hydrogen peroxide as an oxidant is quite helpful to solve the aforementionedproblems . First, due to the excellent kinetics of hydrogen peroxide in the reduction reaction, it is likely to use a non‐noble metal catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Recent studies have shown that the use of hydrogen peroxide as an oxidant is quite helpful to solve the aforementionedproblems. [12][13][14][15] First, due to the excellent kinetics of hydrogen peroxide in the reduction reaction, it is likely to use a non-noble metal catalyst. Second, using non-noble metals shall not catalyze the methanol oxidation so as to avoid the negative effects of MCO.…”
Section: Introductionmentioning
confidence: 99%
“…However, if the suitable hydrogen peroxide conditions (e.g. low concentration and operation temperature) are controlled, the chemical decomposition of hydrogen peroxide is not serious and can be easily handled [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, the investigation of liquid-based FCs employing hydrogen peroxide (H 2 O 2 ) to replace oxygen (O 2 ) as oxidant (e.g. metal semi-FCs, direct borohydride-hydrogen peroxide FCs, direct methanol-hydrogen peroxide FCs, hydrazine-hydrogen peroxide FCs and direct peroxide-peroxide FCs) has been a hot topic [6][7][8][9][10][11][12][13]. Compared with O 2 , the electroreduction of H 2 O 2 takes place via a two-electron transfer involving the breakage of single dioxygen bonds 3 rather than the breakage of double bonds for O 2 reduction [14].…”
Section: Introductionmentioning
confidence: 99%
“…(1); SHE = standardh ydrogen electrode],t he hydrogen peroxide oxidationr eaction (HPOR) occurs,w hich generates protons, electrons, and oxygen. [26] Anode :…”
mentioning
confidence: 99%